10-Hydroxy-2-decenoic Acid, the Major Lipid Component of Royal Jelly, Extends the Lifespan of Caenorhabditis elegans through Dietary Restriction and Target of Rapamycin Signaling. (19th February 2015) - Honda, Yoko; Araki, Yoko; Hata, Taketoshi; Ichihara, Kenji; Ito, Masafumi; Tanaka, Masashi; Honda, Shuji
Abstract : Royal jelly (RJ) produced by honeybees has been reported to possess diverse health-beneficial properties and has been implicated to have a function in longevity across diverse species as well as honeybees. 10-Hydroxy-2-decenoic acid (10-HDA), the major lipid component of RJ produced by honeybees, was previously shown to increase the lifespan of Caenorhabditis elegans. The objective of this study is to elucidate signaling pathways that are involved in the lifespan extension by 10-HDA. 10-HDA further extended the lifespan of the daf-2 mutants, which exhibit long lifespan through reducing insulin-like signaling (ILS), indicating that 10-HDA extended lifespan independently of ILS. On the other hand, 10-HDA did not extend the lifespan of the eat-2 mutants, which show long lifespan through dietary restriction caused by a food-intake defect. This finding indicates that 10-HDA extends lifespan through dietary restriction signaling. We further found that 10-HDA did not extend the lifespan of the long-lived mutants in daf-15, which encodes Raptor, a target of rapamycin (TOR) components, indicating that 10-HDA shared some longevity control mechanisms with TOR signaling. Additionally, 10-HDA was found to confer tolerance against thermal and oxidative stress. 10-HDA increases longevity not through ILS but through dietary restriction and TOR signaling in C. elegans .